DEVELOPMENT OF A MODEL FOR CALCULATING CHANGES IN K76F RAIL STEEL TEMPERATURE TO DETERMINE THE HEAT TREATMENT PARAMETERS - Babachenko, Oleksandr; Kononenko, Ganna; Podolskyi, Rostyslav (Science and Innovation, 2021)
Introduction. The conditions of operation of the railways of Ukraine and the prospects for their entry into the international system of transport corridors require the development and modernization of railway tracks, including rails. Problem Statement. Given the necessity to ensure the main operational parameter of the rails (wear resistance), regulatory and technical documents standardize hardness. The most progressive European standard EN 13674-1-2011 establishes that the hardness of the rail head at a depth of 20 mm shall be, at least, 321 HB, while DSTU 4344:2004 requires, at least, 321 HB at a depth of 11 mm. At the same time, according to EN 13674-12011, the rail surface hardness without the formation of needle structures shall be, at least, 405 HB. Purpose. To determine the possibility of achieving hardness without needle structures for rail head made of steel 0,80% C, 0,25% Si, 0,97% Mn, 0,055% V (hereinafter referred to as K76F), which complies with the world requirements, based on the calcination experiment and calculations with the use of the model; to determine the rational cooling rate for K76F steel during heat treatment. Materials and Мethods. K76F rail steel with 0.80% C, 0.25% Si, 0.97% Mn, 0.055% V. Techniques: metallographic studies, hardness measurements, determination of calcination by end quenching, modeling by means of mathematical calculation with the use of QForm heat treatment software package. Results. The change in temperature, the formation of structure and hardness across the section of a K76F steel sample for calcination tests according to GOST5657 has been modeled. The changes in the hardness and microstructure has been experimentally established, depending on the distance to the heat sink surface; the cooling rate in the points where the hardness meets the requirements of EN 13674-1-2011 for rails has been determined. Conclusions. The analysis of the model has shown a high accuracy of the model and the convergence of the experimental results with the calculated ones. It has been established that the requirements of EN 13674-1-2011 can be achieved up to a hardness of 405 HB without the formation of needle structures on steel that meets the chemical composition of K76F according to DSTU 4344: 2004.